Optimized and scaled-up production of cellulose-reinforced biodegradable composite films made up of carrot processing waste - Otoni, Caio G.; Lodi, Beatriz D.; Lorevice, Marcos V.; Leitao, Renato C.; Ferreira, Marcos D.; Moura, Marcia R. de [UNESP]; Mattoso, Luiz H. C. (Elsevier B.V., 2018)
The ever-growing environmental concern arising from the unrestricted exploitation of fossil sources for the massive production of non-biodegradable materials encourages research on alternative renewable resources. We herein pave the route for the production of biodegradable biocomposites made up of carrot minimal processing waste (CMPW) by optimizing its combination with hydroxypropyl methylcellulose (HPMC) and high-pressure microfluidized cellulose fibers, which played ligand and mechanical reinforcement roles, respectively. Ternary mixture designs established mathematical models aimed at structure-composition-property correlations, allowing their mechanical performances to be innovatively predicted without the need for further experiments. The optimized formulation comprised 33 wt.% CPMW and led to biodegradable biocomposites featuring ca. 30 MPa of tensile strength, ca. 3% elongation at break, and ca. 2 GPa of Young's modulus, properties which are suitable for food packaging applications. Finally, the film-forming protocol was successfully scaled-up through a continuous casting approach, allowing the production of 1.56 m(2) of biodegradable biocomposite in each hour. While scaling up did not affect film's barrier to moisture, it did impair its mechanical behavior.
Keywords: Biopolymer; Cellulose derivative; Biocomposite; Daucus carota L.; Residue; Biodegradability